From Fibrinolysis to the Plasminogen–Plasmin System and Beyond: A Remarkable Growth of Knowledge, with Personal Observations on the History of Fibrinolysis - Kwaan, Hau C. (Seminars in Thrombosis and Hemostasis, 2014)
Great advances have been made in our understanding of the fibrinolytic system from the initial discovery of proteolysis of fibrin by plasmin to the multifaceted and complex role of the plasminogen–plasmin (P–P) system. We now know that the P–P system is composed of several serine proteases and their inhibitors (serpins). This system is involved in many physiological functions, including embryogenesis, cell migration, and wound healing. They also play an important role in the pathogenesis of many diseases, including atherosclerosis, obesity, cancer, and even autoimmune disorders, and neuronal degeneration. Knowledge of their role in cancer enables their use as a prognostic factor. Therapeutic use of various forms of proteases derived from this system has been employed as thrombolytic agents. In addition, small molecules designed to inhibit many of the components of the P–P system are now available for clinical trial, aimed at treatment of these various disorders. The history of such remarkable development of our knowledge on fibrinolysis is reviewed in this article.
Keywords: fibrinolysis; plasminogen; plasminogen activator; PAI-1